SCAR Report 42 - September 2022 - SCAR Data Policy (2022) ... - Research, The Scientific Committee On Antarctic (Zenodo, 2023)
The International Science Council (ISC, formerly ICSU and ISSC) is the parent body of SCAR. In its Assessment on Scientific Data and Information in 2004, the ISC observed that “science has long been best served by a system of minimal constraints on the availability of data and information”, and that a strong public domain for scientific data and information promotes greater return from investment in research, stimulates innovation and enables more informed decision-making. Thus, one of the fundamental recommendations of the assessment is that “ICSU should continue to actively promote the principle of full and open access to scientific data”. Additionally, countries working in the Antarctic operate within the framework of the Antarctic Treaty System. The cornerstone of the system is the Antarctic Treaty, which was signed on December 1, 1959, and came into effect on June 23, 1961. Of particular relevance for polar data management and delivery is Article III, section 1(c), which stipulates that “scientific ...